Narratives of self and traumatic memories (Tempo e Argumento, 2012)
This text was presented as a lecture in the History and Narratives roundtable discussion, during the First International Seminar - History of the Present Time, promoted by the Graduate Program in History of UDESC and ANPUH- Santa Catarina, held on November 7-9, 201, in Florianópolis/SC. It problematizes the subject and its speech, the testimony becomes clear as a narrative and the many possible ways in which the traumatic experience results in narratives of self.
Keywords: narratives of self; traumatic memories; history of the present time